Microwave-Assisted Synthesis of 1,3-Benzothiazol-2(3H)-one Derivatives and Analysis of Their Antinociceptive Activity - Önkol, T.; Dündar, Y.; Yıldırım, E.; Erol, K.; Şahin, M. F (Arzneimittelforschung, 2012)
A rapid and efficient method was developed for synthesis of 6-acyl-1,3-benzothiazol-2(3H)-one derivatives under microwave irradiation (MWI) conditions. The reaction times were shortened compared to conventional heating. Additionally, we synthesized acetic acid and acetamide derivatives of 1,3-benzothiazol-2(3H)-one, 6-acyl-1,3-benzothiazol-2(3H)-one, 5-chloro-1,3-benzothiazol-2(3H)-one and 6-acyl-5-chloro-1,3-benzothiazol-2(3H)-one with the microwave-assisted method and analyzed their antinociceptive activity with the tail flick, tail clip, hot plate and writhing tests. Among the synthesized compounds, 3-[2-(4-ethylpiperazin-1-yl)-2-oxoethyl]-1,3-benzothiazol-2(3H)-one (6a), 5-chloro-3-{2-oxo-2-[4-(propan-2-yl) piperazin-1-yl]ethyl}-1,3-benzothiazol-2(3H)-one (7e) and 3-[2-(4-butylpiperazin-1-yl)-2-oxoethyl]-5-chloro-1,3-benzothiazol-2(3H)-one (8e) showed significant antinociceptive activity in the tail clip, tail flick, hot plate and writhing tests.Supporting Information available online at http://www.thieme-connect.de/ejournals/toc/amf
Keywords: 1,3-benzothiazol-2(3H)-one; tail flick test; tail clip test; hot plate test; writhing test; microwave-assisted synthesis